Politeness Strategies Of Directive Utterance In The Film Of Total Recall And Its Subtitle - Prastiwi, Linda; , Dra. Siti Zuhriah Ariatmi, M.Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research aims at describing the equivalence of the illocution and the politeness strategies of directive utterances in the film of Total Recall and its subtitle. The type of this research is descriptive qualitative research which the writer uses documentation and observation method as the method of collecting data. The data of this research are sentences containing directive utterances and their subtitle. The data sources are films manuscript in both English and Indonesian versions. The result of the research shows that firstly, the equivalent and non equivalent of speaker's illocution of directive utterances. From 48 data finding there are 43 data or 89, 58% are equivalent and 5 data or 10, 42% is non equivalent. The most data equivalent of the speaker's illocution in the form of requesting utterance, 14 data or 29, 17%, while the most data non equivalence of the speaker's illocution in the form commanding and requesting. It has 2 data or 4, 17% of each utterance. Secondly, the equivalent and non equivalent of the politeness strategies of directive utterances. From 48 data finding, there are 44 data (91, 67%) are equivalence and 4 data (8, 33%) are not equivalence. . The most data equivalence of the politeness strategies in the film of Total Recall and its subtitle is in the form bald on record, it is 27 data (55, 25%), while the most data non equivalence of the politeness strategies is in the form bald on record and positive politeness. Each has 2 data or 4, 17%.